2022
DOI: 10.1111/jonm.13688
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of presenteeism in the nursing workforce: A meta‐analysis of 28 studies from 14 countries

Abstract: Aims: This study aimed to estimate the overall presenteeism prevalence in the nursing workforce.Background: Nurses are more prone to presenteeism, which is associated with adverse outcomes for both nurses and patients. However, comprehensive information on the global prevalence of presenteeism in nursing workforce is lacking.Evaluation: Seven databases were systematically searched without year or language restrictions in July 2021. Studies that reported the prevalence rate of presenteeism among nurses were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 52 publications
(67 reference statements)
0
11
0
2
Order By: Relevance
“…The variability of prevalence rates should be explained considering the following elements: (a) sample characteristics (population, response rate), (b) the types of presenteeism studied (sickness, non-sickness, overall), and (c) the variety of measurement instruments [ 17 ]. A recent meta-analysis of 28 studies from 14 countries confirmed that presenteeism is prevalent (estimated at around 49%) among the nursing workforce [ 18 ]. This was “attributable to multiple health conditions and stress; and that it is tied to multiple consequences for the economy, patient safety, and nurse well-being” [ 19 ] (p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…The variability of prevalence rates should be explained considering the following elements: (a) sample characteristics (population, response rate), (b) the types of presenteeism studied (sickness, non-sickness, overall), and (c) the variety of measurement instruments [ 17 ]. A recent meta-analysis of 28 studies from 14 countries confirmed that presenteeism is prevalent (estimated at around 49%) among the nursing workforce [ 18 ]. This was “attributable to multiple health conditions and stress; and that it is tied to multiple consequences for the economy, patient safety, and nurse well-being” [ 19 ] (p. 9).…”
Section: Introductionmentioning
confidence: 99%
“…Presenteeism affects both individuals and organizations. Presenteeism leads to negative consequences among nurses including poor health, limited work ability, low work quality, and adverse patient outcomes (Abdi et al, 2021; Freeling et al, 2020; Min et al, 2022). Measuring presenteeism is particularly important in working environments in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, presenteeism in nursing workforces can be promoted by intense job demands, staff shortages that lead to difficulty in replacing staff, and attitudes staff have toward their own health (Freeling et al, 2020; Johns, 2010; Rainbow & Steege, 2017). Attention to presenteeism in the nursing workforces is particularly important because it not only compromises nurses' health and well‐being but also reduces nurses' ability to provide high‐quality care and thus puts patients at risk (Freeling et al, 2020; Min et al, 2022). For example, nurses' presenteeism has been linked to increased rates of adverse patient outcomes such as rationing of care (Dhaini et al, 2017), patient falls, medication errors (Letvak et al, 2012), and mortality (Trinkoff et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of presenteeism varies from 30% to 90% across professions [ 2 ]. Nurses, compared to other professions, are more prone to this problem [ 3 ]. In China, 94.25% of nurses self-reported that they had been present but unwell within the past 6 months [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scale focuses on presenteeism behavior but does not assess the impacts of presenteeism on work performance or productivity [ 15 ]. A systematic literature review and meta-analysis that examined 28 studies from 14 countries revealed that 50% of nurses showed up for work when unwell or unfit to work and proposed that effective measurement instruments for evaluating presenteeism among nurses and thoughtful solutions to presenteeism are needed [ 3 ]. To date, no gold standard measurement for presenteeism has been developed.…”
Section: Introductionmentioning
confidence: 99%